Nutritional status of school-age children and adolescents in low- and middle-income countries across seven global regions: a synthesis of scoping reviews. Issue 1 (14th January 2023) - Wrottesley, Stephanie V; Mates, Emily; Brennan, Eilise; Bijalwan, Vasundhara; Menezes, Rachael; Ray, Stephanie; Ali, Zakari; Yarparvar, Amirhossein; Sharma, Deepika; Lelijveld, Natasha
Abstract: Objective: To summarise available evidence on the nutritional status of school-age children and adolescents (5–19 years) from seven global regions and on interventions implemented to improve malnutrition in this population. Setting: Global. Design: Findings were compiled from seven scoping literature reviews, including data from low- and middle-income countries within the following UNICEF-defined global regions: East Asia and Pacific; Europe and Central Asia; South Asia; West and Central Africa; Eastern and Southern Africa; Middle East and North Africa and Latin America and the Caribbean. Results: A double burden of malnutrition was evident across the world regions reviewed: stunting, thinness, anaemia and other micronutrient deficiencies persisted, alongside rising overweight and obesity prevalence. Transitions towards diets increasingly high in energy-dense, processed and micronutrient-poor foods were observed. Evidence from intervention studies was limited, but suggested that providing multiple micronutrient-fortified foods or beverages at school may effectively target micronutrient deficiencies and facilitate weight gain in undernourished populations. Interventions to prevent or manage overweight and obesity were even more limited. There was minimal evidence of using novel technological approaches to engage school-age children and adolescents, or of involving them in designing interventions. Conclusion: The limited data available on nutrition of school-age children and adolescents are neither standardised nor comparable. Consensus on methods for assessing nutritional status and its determinants for this age group is urgently needed to set targets and monitor progress. Additionally, strategies are required to ensure that nutritious, safe and sustainable diets are available, affordable and appealing.